Unmanned aerial systems in remotely sensed biomass estimates : how they improve the quality of existing satellite based approaches - Feng, Leon Gaw Yan (2018)
Dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Geospatial Technologies